Recent Advances on the Organocatalytic Asymmetric Aza-Henry Reaction - M.F. Phillips, Ana (Current Organocatalysis, 2016)
Background: The organocatalytic asymmetric aza-Henry (nitro-Mannich) reaction is a powerful tool for the synthesis of enantiopure compounds containing a 1,2-arrangement of stereogenic nitrogen-bearing carbon centers. The products are useful synthetic intermediates which may be easily transformed into a variety of useful substances, with applications in medicine, agriculture and even as ligands or organocatalysts for asymmetric synthesis. Given the usefulness of this reaction and the large body of information published, this review aims to provide readers with an up-to-date account of the latest developments in the field. Methods: The research published on the organocatalytic aza-Henry reaction during approximately the last two years is reviewed. The last comprehensive review dedicated exclusively to this subject was published in March 2013. Results: The main developments which took place during this period were the design of novel catalysts which broadened the scope of the reaction, including some anchored to solid supports, novel activating groups and access to novel targets up to now inaccessible via this route: non-symmetric cis-stilbene diamines, chiral α-amino-β-nitroesters, α-amino-β- nitrophosphonates and functionalized isatin-derived ketimines to name a few. Umpolung chemistry was used to afford peptides bearing aliphatic side chains and it even became possible to carry out asymmetric aza-Henry reactions in the presence of water. The development of new multi-component reactions and domino processes which provided nitrogen heterocycles bearing multiple chiral centers with very high degrees of stereoselectivity continued to be an important addition to the chemist’s repertoire. Conclusion: The developments achieved during this period continue to show the enormous potential of asymmetric organocatalysis and should inspire further work in this area.
Keywords: diamines